Multi-modal with Multiple Image Filters for Facial Emotion Recognition - Huynh, T. Thong (Springer Nature, 2023)
Lecture Notes in Networks and Systems (LNNS, volume 734); CITA: Conference on Information Technology and its Applications; pp: 228-239.